2020
DOI: 10.1371/journal.pbio.3000850
|View full text |Cite
|
Sign up to set email alerts
|

Notch dimerization and gene dosage are important for normal heart development, intestinal stem cell maintenance, and splenic marginal zone B-cell homeostasis during mite infestation

Abstract: Cooperative DNA binding is a key feature of transcriptional regulation. Here we examined the role of cooperativity in Notch signaling by CRISPR-mediated engineering of mice in which neither Notch1 nor Notch2 can homo-or heterodimerize, essential for cooperative binding to sequence-paired sites (SPS) located near many Notch-regulated genes. Although most known Notch-dependent phenotypes were unaffected in Notch1/2 dimerdeficient mice, a subset of tissues proved highly sensitive to loss of cooperativity. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 98 publications
3
31
0
Order By: Relevance
“…NICD dimerization, utilizing two NICDs for gene transcription, is essential for certain NOTCH downstream gene expression. Suppressing of NICD dimerization leads to various developmental disorders including heart anomalies and defective MZB cell differentiation; therefore, shifted balance between dimerized NICD and monomer NICD that can be influenced by NICD dosage is going to affect transcriptional profile as well ( Hass et al, 2015 ; Kobia et al, 2020 ). The changing of gene transcription under different NICD dosages can be further proven by the observation that NICD can change chromatin structure ( Gomez-Lamarca et al, 2018 ), opening of which permits more gene transcription.…”
Section: Mechanisms Underlying Distinct Transcriptional Activation By Different Strengths Of Notch Signalingmentioning
confidence: 99%
“…NICD dimerization, utilizing two NICDs for gene transcription, is essential for certain NOTCH downstream gene expression. Suppressing of NICD dimerization leads to various developmental disorders including heart anomalies and defective MZB cell differentiation; therefore, shifted balance between dimerized NICD and monomer NICD that can be influenced by NICD dosage is going to affect transcriptional profile as well ( Hass et al, 2015 ; Kobia et al, 2020 ). The changing of gene transcription under different NICD dosages can be further proven by the observation that NICD can change chromatin structure ( Gomez-Lamarca et al, 2018 ), opening of which permits more gene transcription.…”
Section: Mechanisms Underlying Distinct Transcriptional Activation By Different Strengths Of Notch Signalingmentioning
confidence: 99%
“…Since Notch1 expression decreases rapidly after β-selection, upregulation of Rag1 / 2 for TCRα rearrangement is likely exerted by other transcriptional factors. Interestingly, when mice harboring Notch1 dimerization mutants were examined for the impacts of dimeric deficiency on multiorgan development, mature T-cell subsets appeared normal, despite the total number of thymocytes declined to some extent ( Kobia et al, 2020 ). Functional validations of mature T cells in these Notch1 dimeric deficient mice are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We then fitted the extracted band intensities to an equilibrium model for binding two sites in a cooperative manner, in a similar way as described in Kobia et al [ 30 ]. In short, the binding probabilities were calculated using standard binding kinetics (Michaelis-Menten).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, reporter assays and/or RT-PCR assays have tested the function of a small subset of these SPS containing enhancers and found that SPSs are typically required for optimal transcriptional responses [25][26][27]29]. A recent study also found that while mice with Notch1 and Notch2 point mutations that abolish cooperative binding to SPSs develop normally under ideal laboratory conditions, stressing the animals either genetically or with parasites can result in profound defects in gastrointestinal, cardiovascular, and immune systems [30]. Collectively, these studies revealed that many Notch-dependent target genes contain SPSs, and that the regulation of dimer-dependent Notch target genes contributes to animal development and homeostasis.…”
Section: Introductionmentioning
confidence: 99%